Comorbidity of hypertension and lung cancer: interplay of genetics and environment - Jingtong Zeng; Difang Shi; Daqian He; Wenxun Dong; Zhenghong Yang; Ying Chen (Discover Oncology)
Abstract Hypertension and lung cancer are two of the most prevalent chronic diseases worldwide, each contributing significantly to public health burdens. While both diseases have been extensively studied individually, their comorbidity remains an underexplored area of research. Recent studies suggest that genetic susceptibility plays a crucial role in the coexistence of these conditions, with overlapping genetic variants influencing both vascular homeostasis and tumorigenesis. The relationship between hypertension and lung cancer is complex, with shared risk factors and common pathogenic mechanisms, including inflammation, oxidative stress, and metabolic dysregulation. Environmental exposures—such as air pollution, tobacco smoke, and heavy metals—can trigger these genetic and epigenetic alterations, thereby increasing susceptibility to both conditions. Beyond genetic predisposition, epigenetic modifications significantly contribute to disease pathogenesis, including DNA methylation, histone modifications, and microRNA (miRNA) regulation. In hypertension, aberrant DNA methylation affects genes involved in vascular remodeling, such as At1b and Scnn1a, influencing blood pressure regulation. Similarly, in lung cancer, tumor suppressor genes such as p16, RASSF1A, and KCNK3 undergo methylation-induced silencing, promoting tumor progression. Histone modifications, particularly histone deacetylase (HDAC) activity, play a key role in both diseases, with HDAC inhibitors like valproic acid showing therapeutic potential in lowering blood pressure and inhibiting lung cancer cell proliferation. Understanding the shared genetic and epigenetic mechanisms between hypertension and lung cancer offers new opportunities for risk prediction, early intervention, and targeted therapies. Future research should focus on integrating genetic screening with environmental risk assessment to develop precision medicine strategies for individuals at high risk of both conditions.